Ribosomopathies: how a common root can cause a tree of pathologies - Nadia Danilova; Hanna T. Gazda (The Company of Biologists, 2015)
Defects in ribosome biogenesis are associated with a group of diseases called the ribosomopathies, of which Diamond-Blackfan anemia (DBA) is the most studied. Ribosomes are composed of ribosomal proteins (RPs) and ribosomal RNA (rRNA). RPs and multiple other factors are necessary for the processing of pre-rRNA, the assembly of ribosomal subunits, their export to the cytoplasm and for the final assembly of subunits into a ribosome. Haploinsufficiency of certain RPs causes DBA, whereas mutations in other factors cause various other ribosomopathies. Despite the general nature of their underlying defects, the clinical manifestations of ribosomopathies differ. In DBA, for example, red blood cell pathology is especially evident. In addition, individuals with DBA often have malformations of limbs, the face and various organs, and also have an increased risk of cancer. Common features shared among human DBA and animal models have emerged, such as small body size, eye defects, duplication or overgrowth of ectoderm-derived structures, and hematopoietic defects. Phenotypes of ribosomopathies are mediated both by p53-dependent and -independent pathways. The current challenge is to identify differences in response to ribosomal stress that lead to specific tissue defects in various ribosomopathies. Here, we review recent findings in this field, with a particular focus on animal models, and discuss how, in some cases, the different phenotypes of ribosomopathies might arise from differences in the spatiotemporal expression of the affected genes.